IMPLEMENTASI METODE DISCRETE WAVELET TRANSFORM (DWT) DALAM SISTEM IDENTIFIKASI TELAPAK KAKI MANUSIA DENGAN KLASIFIKASI SUPPORT VECTOR MACHINE (SVM) - Adinda Maulida; Rita Magdalena; Yunendah Nur Fu’adah (IST AKPRIND Yogyakarta, 2018)
Tvelhe deopment of information and technology have a good impact in modern life. One of them is the introduction of individuals created automatically to facilitate the search for information related to identity. In order not to difficult identification of individuals properly, used methods of recognizing physical characteristics to identify individuals or commonly known as biometrics. Many physical features can be used, such as fingerprints, nasal bones, teeth, and so on as long as they are still members of the body. One is the sole of the foot. Discrete Wavelet Transform (DWT) is a computation method that can be used to support digital identification system. In this study the steps to obtain the parameters required to achieve optimal accuracy include the acquisition of footprint image data, pre-processing, DWT feature extraction to the classification process using the Support Vector Machine (SVM). The process of classification and class determination using SVM algorithm by changing kernel parameters in each test. The highest accuracy of the system used in this final project is the SVM OAO of 72% with the fastest computation time of 66.72 seconds so that the algorithm can be said optimally in the system..